Rheumatoid arthritis-associated interstitial lung disease seen in two generation of females in an Indian family - Shah, Arti D.; Patel, Kaushani H.; Naik, Parshwa; Chakravarti, Chirag H. (International Journal of Research in Medical Sciences, 2023)
Interstitial lung diseases (ILDs) or diffuse parenchymal lung diseases (DPLDs) are a group of lung diseases that is distinguished by subacute or chronic inflammation and/or fibrosis. Family history is currently being considered one of the biggest risk factors for ILD. Rheumatoid arthritis (RA) a systemic autoimmune disease has lungs as its most common extraarticular organ involved. Interstitial lung disease associated with it is one of the major causes of mortality along with severe disability. Lung involvement in RA might appear as ILD, pleural effusion, or pulmonary vasculitis. In this case report a 42-year-old female presented with complain of progressive breathlessness, dry cough, chest pain, joint pain since past 10 years. HRCT Thorax of patient suggested it to be ILD of UIP pattern with raised RF, anti CCP and positivity in ANA profile. Patient had a family history with mother being diagnosed with ILD-NSIP pattern. She was suspicioned for RA as she had complained of small joint pains and swellings and was responding well to steroids and HCQ.